Cytoplasmic microtubules containing acetylated alpha-tubulin in Chlamydomonas reinhardtii: spatial arrangement and properties (The Rockefeller University Press, 1986)
A monoclonal antibody, 6-11B-1, specific for acetylated alpha-tubulin (Piperno, G., and M. T. Fuller, 1985, J. Cell Biol., 101:2085-2094) was used to study the distribution of this molecule in interphase cells of Chlamydomonas reinhardtii. Double-label immunofluorescence was performed using 6-11B-1, and 3A5, an antibody specific for all alpha- tubulin isoforms. It was found that acetylated alpha-tubulin is not restricted to the axonemes, but is also present in basal bodies and in a subset of cytoplasmic microtubules that radiate from the basal bodies just beneath the plasma membrane. Immunoblotting experiments of basal body polypeptide components using 6-11B-1 as a probe confirmed that basal bodies contain acetylated alpha-tubulin. In the cell body, 6-11B- 1 stained an average of 2.2 microtubules/cell, while 3A5 stained an average of 6.5 microtubules. Although exposure to 0 degrees C depolymerized both types of cytoplasmic microtubules, exposure to various concentrations of colchicine or nocodazole showed that the acetylated microtubules are much more resistant to drug-induced depolymerization than nonacetylated microtubules. Axonemes and basal bodies are already known to be colchicine-resistant. All acetylated microtubules appear, therefore, to be more drug-resistant than nonacetylated microtubules. The acetylation of alpha-tubulin may be part of a mechanism that stabilizes microtubules.